IKLIM ORGANISASI TERHADAP STRES KERJA GURU DI SMA SWASTA TERAKREDITASI A SE-KECAMATAN PAMIJAHAN BOGOR - Apriani, Risa; Rahmawati, Ima; awaludin, Muhamad Robie (Institut Agama Islam Sahid (INAIS) Bogor, 2025)
This study aims to examine the influence of organizational climate on teacher work stress in three accredited private senior high schools (A-rated) in Pamijahan District, Bogor Regency. Using a quantitative approach with a survey design and total sampling technique, 56 full-time foundation teachers participated as respondents. Data were collected through a closed-ended questionnaire, which had been tested for validity and reliability. The data were analyzed using simple linear regression with SPSS. The results indicate that teachers’ perceptions of the organizational climate fall into the very good category, while the level of work stress is categorized as very high. Regression analysis reveals a significant effect of organizational climate on teacher work stress, with a coefficient of determination of 65%, suggesting that a substantial portion of the variance in work stress can be explained by differences in perceived organizational climate. These findings underscore the critical role of work environment quality in influencing teachers’ psychological well-being. However, the results also show that, in addition to organizational climate, other factors contribute to teacher stress but were not explored in this study. Therefore, future research is recommended to examine additional variables to gain a more comprehensive understanding of work stress dynamics in educational settings.